Drama-based mobile phone-delivered virtual learning as a way to support improved biosecurity in smallholder pig farming - Chenais, E.; Fischer, K.; Kagolobya, R.; Dione, Michel M.; Ståhl, K.; Sternberg-Lewerin, S. (Springer, 2025)
This study describes a novel approach for delivering knowledge to pig producers about preventing African swine fever in domestic pigs: a virtual learning course consisting of audio recorded drama sketches, employed to support improvements in implementation of biosecurity in smallholder pig farming in Uganda. The course was delivered via system-generated, automated mobile phone calls. Participation was automatically registered and followed up by an interview with the objectives to investigate the usability as well as the potential of this type of learning for instigating change. The 155 participants were active at different nodes of the smallholder pig value chain, and in total 148 of these could be reached for an interview. Results were both quantitative and qualitative. They were analysed by descriptive statistics and thematic analysis respectively. All participants completed the first audio, and 121 participants completed all ten audios. Almost all interviewees said that they had learned something new, and reported to have implemented some changes in their pig management or disease prevention routines. Three dominant topics emerged from the thematic analysis concerning what interviewees reported that they had learned, what they considered important and what they had changed/not changed: “cleanliness”, “separation of pigs” and “general pig health”. These dominant topics support recent calls for mainstreaming ASF prevention into general herd health messages. We conclude that the interactive learning course was appreciated by those reached by it and led to widespread reporting of new and relevant knowledge gained about ASF. As such, a virtual learning course could be an important complement to other forms of advisory services on ASF.